Self-Healing Coatings Based on Stimuli-Responsive Release of Corrosion Inhibitors: A Review - Zhang, Yue; Yu, Mei; Chen, Chao; Li, SongMei; Liu, JianHua (Frontiers in Materials, 2022)
Corrosion inhibitors loaded in coatings promote the protection performance of coatings, avoid the local corrosion of metal substrates, and endow the self-healing properties of the coatings. The stimuli-responsive release of corrosion inhibitors, which is generally achieved by loading corrosion inhibitors in containers, is key to the self-healing and long-term protection of the coatings. The loading and release methods of corrosion inhibitors are discussed in the article. First, two kinds of loading methods for corrosion inhibitors are reviewed, which are one-step synthetic methods and multistep synthetic methods. Then the released methods of corrosion inhibitors, which can be achieved by intrinsic properties and surface modification of containers, are summarized.